White-Footed Ant, Technomyrmex albipes (Fr. Smith) (Insecta: Hymenoptera: Formicidae: Dolichoderinae) - Jack Warner; Rudolf H. Scheffrahn; Brian Cabrera (EDIS)
The white-footed ant, Technomyrmex albipes (Fr. Smith) has been making news in Florida over the last few years as a pest ant of major importance. Pest control companies, the media and homeowners continually consult universities and government agencies for information on how to control this nuisance ant. This report provides recent information (August 2002) on the distribution and habits of the white-footed ant (WFA) in Florida and the research being conducted on improved control practices. This document is EENY-273, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2002.